2005
DOI: 10.2174/0929866053765752
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Its Analogs, Methyl-Substituted in Ortho-, Meta- or Para- Position of Aromatic Ring of Phenylalanine in Position 2: NMR Study and Biological Activities

Abstract: Complete analyses of NMR data of oxytocin (OT) and 4 analogues, ([o-MePhe(2)]OT, [mMe-Phe(2)]OT, [m-OMePhe(2)]OT and [p-MePhe(2)]OT), are given. The same conformational behavior in solution on one hand and large differences in biological activities on the other hand indicate that the compounds adopt a "biologically active conformation" at the stage of interaction with the receptor when the character of the substituent and its position on the aromatic ring may play a role in hindering attaining the ideal comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[9,10] Two hydrogen bonds, the NH of Tyr-2 with the CO of Asn-5 and the NH of Asn-5 with the CO of Tyr-2, correspond to those of OXT in DMSO solution. [6] In conclusion, NMR analysis of OXT in phosphate buffer pH 6.2 using presaturation NOESY NMR techniques was effective and resulted in complete assignments of 1 H, 13 C, and 15 N NMR spectra including 1 H and 15 N of amide and amino groups. In the case of OXT without 15 N enrichment, 1 H-15 N HSQC NMR has proven to be a useful spectral tool to determine 15 N of amide and amine groups by means of correlation with their 1 H assigned by COSY and HMBC.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…[9,10] Two hydrogen bonds, the NH of Tyr-2 with the CO of Asn-5 and the NH of Asn-5 with the CO of Tyr-2, correspond to those of OXT in DMSO solution. [6] In conclusion, NMR analysis of OXT in phosphate buffer pH 6.2 using presaturation NOESY NMR techniques was effective and resulted in complete assignments of 1 H, 13 C, and 15 N NMR spectra including 1 H and 15 N of amide and amino groups. In the case of OXT without 15 N enrichment, 1 H-15 N HSQC NMR has proven to be a useful spectral tool to determine 15 N of amide and amine groups by means of correlation with their 1 H assigned by COSY and HMBC.…”
Section: Resultsmentioning
confidence: 90%
“…The results of NOE cross-peak patterns in phosphate buffer are different from that in DMSO solution suggesting that the conformation of OXT is different between phosphate buffer and DMSO solution. [6] The thermal coefficient values, δNH/ T, for peptide amide proton resonances, which offer information about contributions of amide protons to hydrogen bonds, were obtained from the shift variations occurring when the temperature was increased from 25 to 40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OT hormone has been known to be of the topic of immense investigation in lieu of its biological functions such as the maintenance of labor and milk ejection in mammals (Gimpl & Fahrenholz, 2001), facilitating the sexual maturation (Parent et al, 2008), stimulating the pre-ovulatory luteinizing hormone surge (Rettori, Canteros, Renoso, Gimeno, & McCann, 1997), and also its biomedical application such as in the treatment of autism (Newschaffer et al, 2007). Toward understanding the biological activities of OT, various works have been reported to be carried out for studying the interactions of OT with neurophysin (Blumenstein, Hruby, Viswanatha, & Chaturvedi, 1984;Eubanks, Lu, Peyton, & Breslow, 1999;Live, Cowburn, & Breslow, 1987;Rose, Wu, Hsiao, Breslow, & Wang, 1996) and with receptor (Bélec, Blankenship, & Lubell, 2005;Budesínsky, Procházka, & Slaninová, 2005;Carnazzi et al, 2001;Lebl et al, 1990;Lubecka, Sikorska, Marcinkowska, & Ciarkowski, 2014;Sikorska & Kwiatkowska, 2013;Turner, Matsoukas, & Moore, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the difficulty in obtaining NMR spectra sufficient for precise elucidation of the conformations of OT in water (Feeney, Roberts, Rockey, & Burgen, 1971;Glickson et al, 1976), the conformational studies of OT by NMR have been shown to be readily performed in DMSO (Ballardin et al, 1978;Bhaskaran et al, 1992;Kato et al, 1993;Wittelsberger, Patiny, Slaninova, Barberis, & Mutter, 2005) and revealed that the assignment of almost all of the 1 H and 13 C resonances of OT can be obtained in DMSO solvent (Budesínsky et al, 2005;Kato et al, 1993;Ohno, Kawasaki, Okuda, & Yamaguchi, 2010) . So, the study of the cyclic part of OT in DMSO solution rather than in water is desirable.…”
Section: Introductionmentioning
confidence: 99%